Role of disclinations around kink bands on deformation behavior in Mg–Zn–Y alloys with a long-period stacking ordered phase. (15th April 2023) - Tokuzumi, Tsubasa; Mitsuhara, Masatoshi; Yamasaki, Shigeto; Inamura, Tomonari; Fujii, Toshiyuki; Nakashima, Hideharu
Abstract: Mg–Zn–Y alloys that contain an Mg-based long-period stacking ordered (LPSO) phase exhibit excellent mechanical properties because of the kink bands formed by plastic deformation. Such "kink-band strengthening" has attracted significant attention. Herein, we conducted deformation tests on directionally solidified single-phase LPSO Mg85 Zn6 Y9 alloys to investigate the kink-band strengthening mechanism. High-angular resolution electron backscatter diffraction was performed to detect misorientation between the matrices on either side of the kink bands. The misorientations corresponded to the magnitudes of the Frank vectors of the disclinations around the kink, and closely matched the estimations from geometric analysis, which supported the existence of disclinations. Moreover, the Frank vector of the kink bands increased after shear deformation, which indicates that shear deformation introduced new disclinations around the kinks. Scanning electron microscopy demonstrated that the kinks clearly obstructed basal ⟨ a ⟩ slip. Furthermore, scanning transmission electron microscopy of a sheared kink band revealed dislocation pile-ups on both sides of the kink/matrix interface, as well as the formation of secondary kinks that stabilized the structure against shear deformation (i.e., self-accommodation) and bend contours caused by elastic stress fields. The results suggest that disclinations behave as long-range obstacles to dislocation motion (e.g., by reducing the increase in kink-band self-energy or by the elastic stress field of disclinations). We believe that this study will play a key role in identifying the factors responsible for kink-band strengthening in LPSO-phase Mg alloys and in understanding the phenomena underlying the strengthening mechanism. Graphical abstract: Image, graphical abstract